Combined cooling heating and power systems: Sustainability assessment under uncertainties. (15th November 2017) - He, Chao; Zhang, Quanguo; Ren, Jingzheng; Li, Zhaoling
Abstract: Combined cooling, heating, and power (CCHP) systems have been recognized as a promising technology for energy efficiency improvement and emissions mitigation. This study aims at developing a multi-criteria sustainability assessment method to prioritize the alternative CCHP systems under uncertainties. An interval analytic network process (ANP) that can address the vagueness, ambiguity, and subjectivity existing in human judgments and consider the interdependences and interactions among the evaluation criteria was used to determine the weights of the criteria for sustainability assessment, and an interval analytic hierarchy process (AHP) which is a structured technique for organizing and analyzing complex decisions was also employed to quantify the relative performances of the alternative CCHP systems with respect to the soft criteria. An interval technique for order of preference by similarity to ideal solution (TOPSIS) was employed to rank the alternative CCHP systems according to their sustainability. An illustrative case including five CCHP systems has been studied using the proposed method. A solid electrolyte fuel cell (SOFC) combined with a waste heat afterburning absorption refrigerator was recognized as the most sustainable scenario. In addition, the results have been further investigated through sensitivity analysis and validated by the weighted sum method. Highlights: Data with respect to soft criteria were quantified by interval AHP method. Interval ANP was used to determine the weights of the criteria. Interdependences and interactions among the criteria can be incorporated. Interval TOPSIS method was used to determine the sustainability sequences. Uncertainties can be incorporated for sustainability assessment of CCHP systems.